2018
DOI: 10.5505/pajes.2017.82574
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of geotechnical properties and bearing capacity performance of blast furnace slag

Abstract: Bu çalışmada, yüksek fırın cürufunun (YFC) geoteknik özellikleri incelenmiş ve taşıma kapasitesi performansı analiz edilmiştir. Dane boyutunun taşıma kapasitesi üzerindeki etkisini araştırmak amacıyla YFC ince (Dmax = 4.75 mm) ve iri (Dmax = 9.50 mm) dane dağılımlı olarak iki bölüme ayrılmıştır. YFC'nin dane boyu dağılımı, özgül yoğunluk, pH, optimum su içeriği, maksimum kuru birim hacim ağırlık ve kıvam limitleri gibi temel mühendislik özellikleri ASTM standartlarına uygun olarak belirlenmiştir. Daha sonra, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…The cohesive soil and BFS mix lower the liquid and plasticity limits [ 65 ]. The internal friction angle of BFS is 39°–43°, and specific gravity is between 2.29 up to 3.35 [ 63 , 66 , 67 ]. The CBR tests on BFS have shown that the bearing capacity is dependent on soil arrangement and inter-particle forces like matric suction and dilatancy).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cohesive soil and BFS mix lower the liquid and plasticity limits [ 65 ]. The internal friction angle of BFS is 39°–43°, and specific gravity is between 2.29 up to 3.35 [ 63 , 66 , 67 ]. The CBR tests on BFS have shown that the bearing capacity is dependent on soil arrangement and inter-particle forces like matric suction and dilatancy).…”
Section: Resultsmentioning
confidence: 99%
“…The CBR tests on BFS have shown that the bearing capacity is dependent on soil arrangement and inter-particle forces like matric suction and dilatancy). The BFS CBR bearing capacity is between 65% to 160% for standard and modified Proctor compaction technique [ 67 ].…”
Section: Resultsmentioning
confidence: 99%